Comparison of efficacy of PGE2 tablets vs combination of PGE2 tablets with cervical foleys in predicting the outcome of induction of labor - Attayaba Khan; Rabia Mohsin; Mehnaz Khakwani; Nabila Tariq; Ayema Shabbir; Iqbal, Muhammad (Medical Journal of South Punjab, 2024)
Objective: To determine the comparison of effectiveness of PGE2 tablets alone vs combination of PGE2 tablets with cervical Foleys in predicting outcome of labor.Methods: Study was conducted on 200 women enrolled according the inclusion and exclusion criteria. Simple random sampling was performed. Group 1 was induced using a vaginal prostaglandin E2 pessary, and Group 2 was induced using a combination of both PGE2 cervical Foleys catheter. The cost, the amount of time between induction and delivery, and the success rate of delivery were tracked and compared between the two approaches.Results: The total of 200 female pregnant women was included. Mean age of the respondents was 25.16 + 3.3 years. PGE 2 labor induction time was 8.44+3.19 hours’ vs combination use of PGE2 and cervical Foleys catheter time came as 14.67 + 6.36 hours. A statistical difference between them was found p